Investigation of the Optimal Ratio of Rice Flour, Tapioca Starch, and Cornstarch on the Quality of Chiu Chow Dumplings by Mixture Design - Jaikaew, Thappasarn; Wongtom, Rungtip; Sonkitdee, Suntorn; Subanmanee, Natthaporn (PKRU SciTech Journal, 2023)
The objective of this research is to investigate the effect of the optimum content of rice flour, tapioca starch, and cornstarch on the quality of Chiu Chow dumplings using a mixture design. The determination of physical properties found that, the brightness value (L*) and the red value (a*) increased with an increase in tapioca starch, however ∆E was low which same as the standard formula (formula No. 3). In contrast, the yellow value (b*) decreased. Furthermore, as the amount of tapioca starch increased, the cutting force and the viscosity of the starch increased. The determination of sensory evaluation found that the average scores in the characteristics of transparency, viscosity, softness, and overall preference of samples were significantly different (p≤0.05) and that the samples with the highest score were those of the experimental formula 6 that have a ratio of rice flour : tapioca starch : cornstarch of 40 : 50 : 10 g, respectively. According to consumer acceptance of samples, it was found that the transparency of the standard formula was more acceptable than the experimental formula, but the softness of the experimental formula 6 was more acceptable than the standard formula (formula No. 3). However, the viscosity and overall preference of both formulations were not significantly different (p>0.05). A comparison of the cost prices of production found that the experimental formula had a lower cost prices than the standard formula.